Paclobutrazole, NAA and GA3 Effects on Growth and Dry Matter Partitioning of Andrographis paniculata Nees. - Shekhada, Raxit R.; Macwan, Sunil J.; Singh, T. Amarjeet (International Journal of Economic Plants, 2022)
Andrographis paniculata is an important medicinal plant which possesses many medicinal applications. Looking to the importance of plant growth regulators one study was carried out on the influence of foliar spraying treatments in the yield of Kariyatu. Different treatments which includes NAA (50,100 and 200 mg l-1) , GA3 (50,100 and 200 mg l-1) and Paclobutrazol (50,100 and 200 mg l-1) with one as control were considered as foliar application at 30 days after transplanting. Experimental results indicated leaf, shoot and total dry matter increased in all the treatments progressivelly upto harvest but root-shoot ratio decreased with increase crop growth stage that means high proportion of shoot is increases. Leaf area duration was increased progressively up to 75–105 days after transplanting and thereafter declined while crop growth rate was shown increased up to 45–75 days after transplanting then decreased during the 75–105 days after transplanting which means after reproductive stage to maturity phase of growth, crop growth rate decline. The biomass duration was increased with age of the crop till harvest. Significantly positive effect was reported in GA3100 mg l-1 and lowest result was found in control. The translocation process must have been more prominent in the foliar spraying of GA3 100 mg l-1 than rest of the treatments indicates that photosynthesis and translocation efficiency increases by foliar spraying treatments with growth regulators. GA3 100 mg l-1 is efficient in dry matter production and its partitioning in leaves, stem as compared to other treatments.